2023
DOI: 10.2105/ajph.2022.306839
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic, Socioeconomic Effects, and Intimate Partner Violence Against Women: A Population-Based Cohort Study in 2020, Iran

Abstract: Objectives. To investigate the prevalence, pattern, and socioeconomic risk factors of intimate partner violence (IPV) before and 6 months after the pandemic onset among a cohort of Iranian women. Methods. We conducted a population-based IPV survey among 2502 partnered Iranian women aged 18 to 60 years before (n = 2502) and 6 months after (n=2116) the pandemic’s onset. We estimated prevalence and incidence of psychological, physical, and sexual IPV, and the odds of different forms of IPV associated with main e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Although the majority of IPV research focuses on physical abuse, Sahraian et al (2015) found that between 50% and 66% of married women with psychiatric hospitalized husbands experienced characteristics of economic abuse at least “sometimes.” Despite recent efforts to advance the nation’s response to IPV, no national policies or laws have been enacted to protect victims (Ghaffarihosseini et al, 2021). Furthermore, Iran saw a significant rise in the prevalence rate of IPV following the coronavirus (COVID-19) pandemic (Fereidooni et al, 2023), highlighting the urgent need for victim protection. Furthermore, there are a limited number of adequate and culturally compatible measures in Iran to assess spousal abuse in all of its forms (Sotoodeh Ghorbani et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of IPV research focuses on physical abuse, Sahraian et al (2015) found that between 50% and 66% of married women with psychiatric hospitalized husbands experienced characteristics of economic abuse at least “sometimes.” Despite recent efforts to advance the nation’s response to IPV, no national policies or laws have been enacted to protect victims (Ghaffarihosseini et al, 2021). Furthermore, Iran saw a significant rise in the prevalence rate of IPV following the coronavirus (COVID-19) pandemic (Fereidooni et al, 2023), highlighting the urgent need for victim protection. Furthermore, there are a limited number of adequate and culturally compatible measures in Iran to assess spousal abuse in all of its forms (Sotoodeh Ghorbani et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings revealed that women with poor economic status were three times more likely to experience violence compared to women with good economic status. The association between domestic violence and poor economic status has been consistently supported by previous studies 28,32,37 . The risk factors for domestic violence, such as unemployment, limited resources, and restricted social support are further exacerbated by the measures implemented to address the Covid‐19 pandemic 3 .…”
Section: Discussionmentioning
confidence: 67%
“…The association between domestic violence and poor economic status has been consistently supported by previous studies. 28 , 32 , 37 The risk factors for domestic violence, such as unemployment, limited resources, and restricted social support are further exacerbated by the measures implemented to address the Covid‐19 pandemic. 3 Evidence has shown that women face a higher risk of violence when confined with little access to law enforcement agencies due to lockdown measures.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we surveyed residents of Germany, a high-income country. Our results are therefore not generalizable to middle- or low-income countries where violence-related risk factors such as job loss and resulting financial worries, which were enhanced as a result of the pandemic, might have had an even greater impact on the population (Fereidooni et al, 2021). Since our study is part of a larger survey, variables that would have allowed consideration of sociocultural influences (e.g., sexual orientation, gender identity, culture, religion, or ethnicity) were not explicitly recorded.…”
Section: Discussionmentioning
confidence: 69%
“…According to the authors, no significant changes were found in the 12 - month prevalence of either IPV or VAC. Moreover, one study that surveyed a representative sample of Iranian women before and during the pandemic found a relative increase of more than 20.0% for physical, psychological, or sexual IPV as well as an incidence of first-time experience of violence during the pandemic of 25.5% (Fereidooni et al, 2021).…”
Section: Introductionmentioning
confidence: 99%